2006
DOI: 10.1158/1055-9965.epi-05-0890
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Comparison of Aflatoxin B1 Serum Albumin Adducts in Humans by Isotope Dilution Mass Spectrometry and ELISA

Abstract: Metabolic activation of the hepatocarcinogenic mycotoxin aflatoxin B 1 (AFB 1 ) results in the covalent attachment of AFB 1 to serum albumin. Digestion of adducted albumin releases AFB 1 -lysine, a biomarker of exposure status. AFalbumin adducts have been most frequently measured in precipitated serum albumin using an immunoassay (ELISA); however, a sensitive and specific isotope dilution mass spectrometric (IDMS) assay for measurement of AFB 1 -lysine in serum has recently been developed. The ELISA and IDMS m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 24 publications
2
46
0
Order By: Relevance
“…Because the present study represents an extreme range of adduct levels, the curve was truncated to ELISA concentrations of 500 pg/mg albumin for the purpose of comparison and the regression analysis was repeated (n = 39). The slope of this line was 2.53 with a correlation coefficient of 0.86 and an intercept of 0.014 ng/mg albumin, within experimental error of the slope obtained previously (16).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Because the present study represents an extreme range of adduct levels, the curve was truncated to ELISA concentrations of 500 pg/mg albumin for the purpose of comparison and the regression analysis was repeated (n = 39). The slope of this line was 2.53 with a correlation coefficient of 0.86 and an intercept of 0.014 ng/mg albumin, within experimental error of the slope obtained previously (16).…”
Section: Discussionsupporting
confidence: 87%
“…In addition, the AF-lys levels were again far lower in the earlier study (17). The higher response of the ELISA method relative to chromatographic methods has been reported previously (16)(17)(18). The chromatographic methods are expected to measure only the concentration of AF-lys.…”
Section: Discussionmentioning
confidence: 73%
“…Aflatoxin-albumin adduct concentrations measured by ELISA are well correlated with AFB 1 -lys concentrations measured by HPLC-fluorescence and IDMS, albeit the levels obtained in a recent study found that values using an ELISA were 2.6-fold higher than those measured in the same samples by IDMS (12,13). The AFB 1 -lys adduct has been shown to be present in rat albumin by full scan and tandem mass spectrometry, such confirmatory spectra have not been reported for human albumin samples collected in exposed populations (8,13).…”
Section: Introductionmentioning
confidence: 88%
“…Immunoassays, high-performance liquid chromatography (HPLC) with fluorescence detection, and isotope dilution mass spectrometry (IDMS) have been used to measure serum albumin adduct concentrations and assess aflatoxin exposure status in epidemiologic studies (9)(10)(11)(12). Aflatoxin-albumin adduct concentrations measured by ELISA are well correlated with AFB 1 -lys concentrations measured by HPLC-fluorescence and IDMS, albeit the levels obtained in a recent study found that values using an ELISA were 2.6-fold higher than those measured in the same samples by IDMS (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Many different analytical methods are now available for quantitation of chemical adducts in biological samples, each with unique specificity and sensitivity (Santella, 1999;Poirier, 2004;Wogan et. al., 2004;Scholl et. al., 2006).…”
Section: Biomarkers and Immunoassaysmentioning
confidence: 99%